Challenge of integrated low-cost emission monitoring system into a digital information system. Issue 1 (January 2021) - Simbolon, A M; Fatkhurrahman, J A; Mariani, A; Sari, I R J; Syafrudin,; Sudarno,
Abstract: The emission from industry has become a significant problem in Indonesia. Usually, the enterprise uses an accredited testing laboratory to conduct emission tests to report its process's environmental performance. In contrast, this testing was accurate, but it cannot visualize whole time emission from one method. This year, the Covid-19 pandemic also gained some difficulties in environmental evaluation in the industry, including emission performance evaluation. Some big companies may have expensive continuous emission monitoring that can substitute manual laboratory testing. Some other, the small and medium scale industry did not have this system. There is a possible development of an integrated low-cost emission monitoring system in the small-medium scale industry. The low-cost gas sensor rapidly develops and gets more accurate. An engineering scenario of integrating low-cost emission monitoring systems into digital information systems could be developed under some challenges, instrumentation, calibration, and regulative support. By applying this scenario, periodical emission concentration can be evaluated periodically to support air quality management policy.